LINGUOPRAGMATIC FEATURES OF THE FUNCTIONING OF STYLISTIC DEVICES IN THE SENSE FIELD OF G. DELEDDA’S NOVEL OF DECADENCE “THE IVY” - Okhrimenko, Valeriia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
The article focuses on linguopragmatic potential of functioning of stylistic devices in the sense field of G. Deledda’s novel of decadence "The Ivy". It has been established that the system of stylistic devices reflects the author’s intention to show disappointment, hopelessness, the crisis of the social system and the decline of the noble families of Sardinia by creating the semantic field of tension within the body of all the text. The semantic field of the decadence novel “The Ivy” is based on polarized reference groups associated with subjects-characters belonging to higher vs. lower social stratum being the last one the background for their characterization. The regularities of information quantization are based on the cognitive principle of salience. The polarized evaluation (negative vs positive) is determined by the nucleus of reference group – subject (character) belonging respectively to higher vs lower social stratum. The reference group has a field structure. The nucleus of the reference group is a subject (character) belonging to a higher vs. lower social stratum, the pre-nuclear zone – his place of residence, surrounding objects, landscape. The nucleus of the reference group determines the spreading of the semantic space in a certain direction depending on the evaluation of the character and sets the direction of the typification of the conditions of meaning creation. The semantic field of tension within the body of all the text is created by peculiarities of functioning of stylistic devices being extended antithesis the most important of them that includes simile, personification and epithet. In the macroact of description, verbs of semantics of movement being part of stylistic device of personification can acquire a negative evaluation as well as locative markers being part of extended antithesis. In the semantic space of G. Deledda’s novel “The Ivy” denotative lexical units (evaluatively neutral vocabulary) can acquire a negative evaluative meaning under the influence of sense field. Reference groups consisting of subjects-characters belonging to a higher social stratum and their immanent property – the inability to take decisive action determine the verbalization of the system-forming meanings of negative possibility. Simile being one of the most used stylistic devices is used to denote negative emotions, negative states, lack of vitality, inability to control the situation. Color symbolism is used in G. Deledda’s novel of decadence "The Ivy". Light and dark colors are used as part of extended antitheses that include epithets. Antithesis with color symbolism are mostly used to describe the appearance of characters. Dark colors contrast with light colors, while light colors being part of antithesis acquire a negative evaluation due to associative semantic series. ____________ References: • Manakin, V. M. The contrastive lexicology (K.: Znannya, 2004), 326. • Okhrimenko, V. I. Linguopragmatic features of the meaning field of descriptive texts (on the material of description of the character of Unknown in the novel of A. Manzoni “Bethrothed”) Problems of semantics, pragmatics and cognitive linguistics 45 (2024):79-93. • Okhkimenko, V. I. Linguopragmatic features of the functioning of affixal derivatives in the meaning field of L Capuana’s novel “The Marquis of Roccaverdine” Problems of semantics, pragmatics and cognitive linguistics 44 (2023): 103-115. • Okhrimenko, V. I. Ontology and Gnoseology of the Category of Modality in Italian: DSc thesis, Kyiv University, 2012, 612. • Syz’ko, G. Worldview and aesthetic shifts in art and literature of the mid-second half of the 19th century: https://www.slideshare.net/slideshow/xix-55919192/55919192 (accessed 15.10.24). • Word. Sign. Discourse. An anthology of world literary and critical thought of the 20th century, edited by Maria Zubrytska (Lviv, Litopys, 1996), 633. • Fillmore, Ch. Frame semantics and the nature of language «Annals of the New York Academy of Sciences: Conference on the Origin and Development of Language and Speech» 280 (1976): 20-32. • Lala L. Tipi e generi testuali: https://www.treccani.it/enciclopedia/tipi-di-testo_(Enciclopedia-dell’Italiano)/ (accessed 27.02.24). • Deledda, L’Edera. (Milano: Mondadori, 1950), 219.